Predicting satisfaction with vocational status among people with serious mental illness in vocational services: the role of perceived skills and support - Gili Hoter Ishay; Gili Hoter Ishay; Gil Goldzweig; Ilanit Hasson-Ohayon; Marc Gelkopf; Efrat Shadmi; David Roe (Frontiers in Psychiatry)
BackgroundThis study aimed to explore the role of perceived skills and support in satisfaction with vocational status to better address the vocational needs and recovery goals of individuals with serious mental illness (SMI). It focuses on three service types: individual placement and support (IPS), sheltered workshops, and vocational support centers.MethodThe study is a cross-sectional analysis of the nationwide Israeli PR-PROM project data. A sample of 2,968 participants diagnosed with SMI and their service providers self-reported their perceived skills, support, and satisfaction with vocational status.ResultsWe found perceived skills and support to be primary predictors of vocational satisfaction across all groups. There were significant differences in satisfaction with vocational status among the three service types: IPS users reported higher satisfaction than sheltered workshop and vocational support center users. The service-provider evaluations reflected similar trends, with higher satisfaction ratings for more integrative services. Additionally, discrepancies were observed between participant and provider satisfaction ratings, varying by vocational service type.DiscussionThe study highlights the importance of perceived skills and support in enhancing satisfaction with vocational status for people with SMI regardless of the vocational service type. Whereas objective factors like employment status and salary contribute to vocational rehabilitation and quality of life, subjective perceptions of skills and support play a significant role in satisfaction with vocational status. The results suggest that vocational rehabilitation services should monitor consumers’ perceptions of skills and support to improve their vocational satisfaction, which can promote personal well-being and social integration.